2006
DOI: 10.1134/s0006297906030151
|View full text |Cite
|
Sign up to set email alerts
|

Determination of binding constants of lipopolysaccharides of different structure with chitosan

Abstract: The interaction of endotoxins--lipopolysaccharides (LPS) different in degree of the O-specific chain polymerization--with 20- and 130-kD chitosan was studied using the competitive binding of LPS with the complex of chitosan-anionic dye (tropaeolin 000-2) and the direct binding of (125)I-labeled LPS with chitosan immobilized on Sepharose 4B. The interaction of 20-kD chitosan with LPS was non-cooperative, and immobilization of the polycation on Sepharose resulted in its binding to (125)I-labeled LPS with a posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 16 publications
3
11
0
Order By: Relevance
“…This fact is well in accord with our earlier data which showed that the affinity of LPS-chitosan binding and the number of binding sites are determined by the length of the О-specific polysaccharide of Y. pseudotuberculosis LPS [30]. At the same time in contrast to the E. coli LPS, Y. pseudotuberculosis LPS with the same length of O-specific chains has the K b = 2.8 ⁎ 10 5 M [30]. It is a reflection of features of lipid component of these LPS namely fatty acid arrangement of lipid A or/and features of structure of core region studied LPS and would be objects of future investigations.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This fact is well in accord with our earlier data which showed that the affinity of LPS-chitosan binding and the number of binding sites are determined by the length of the О-specific polysaccharide of Y. pseudotuberculosis LPS [30]. At the same time in contrast to the E. coli LPS, Y. pseudotuberculosis LPS with the same length of O-specific chains has the K b = 2.8 ⁎ 10 5 M [30]. It is a reflection of features of lipid component of these LPS namely fatty acid arrangement of lipid A or/and features of structure of core region studied LPS and would be objects of future investigations.…”
Section: Discussionsupporting
confidence: 91%
“…coli LPS has the highest affinity to chitosan (K b = 7.95 ⁎ 10 5 M), which is ten times more than the chitosan binding affinities of P. vulgaris and Y. pseudotuberculosis LPSs. This fact is well in accord with our earlier data which showed that the affinity of LPS-chitosan binding and the number of binding sites are determined by the length of the О-specific polysaccharide of Y. pseudotuberculosis LPS [30]. At the same time in contrast to the E. coli LPS, Y. pseudotuberculosis LPS with the same length of O-specific chains has the K b = 2.8 ⁎ 10 5 M [30].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The apparent binding constant value ( K a ) of chitosan with LPS was determined to be approximately 10 5 M −1 , which was in line with literature data on the binding constants of LPS complexes with other polycations, such as human serum albumin [31] and NK-lysine [32]. At saturation, there were 9–11 and 200 glucosamine residues per mole of LPS on average in the complexes formed in dilute solutions (LPS concentration <0.1 mg/mL) [33] and in concentrated solutions (LPS concentration 1 mg/mL) [34], respectively. The stoichiometry of chitosan-LPS complexes and the K a values were dependent on the reaction conditions, including the temperature, component concentration, pH and ionic strength of solutions.…”
Section: Lipid a Chitosan And Carrageenan—marine Compounds With Asupporting
confidence: 84%
“…The former includes receptors monoclonal antibodies (Adachi et al, 1999) and cationic peptides (Nagaoka et al, 2001), while the latter includes PMB and synthetic peptides (Hwang et al, 2007;Lin et al, 2008). Chitosan, a polysaccharide larger than COS, has been reported to interact with LPS and produce a stable complex due to polycation and hydrophobic substituents (Davidova, Naberezhnykh, Yermak, Gorbach, & Solov'eva, 2006;Davydova et al, 2008;Yermak et al, 2006). But this interaction is much more weaker than PMB, and needs more than 18 h to form the complex , and water soluble derivatives of chitosan with hydrophobic substituent and low substitution extent of amino group have better activity to binding endotoxin (Naberezhnykh, Gorbach, Likhatskaya, Davidova, & Solov'eva, 2008).…”
Section: Discussionmentioning
confidence: 99%